PERANAN BRAND ENDORSER DAN PERSONAL BRANDING PUSTAKAWAN DALAM MEMBANGUN CITRA PERPUSTAKAAN: DALAM TINJAUAN KOMUNIKASI - Yunus Winoto (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2016)
Building a positive image of an institution or a company is important to gain recognition among soci- ety. Image is a perception that comes from the society. However, it is also determined by the institution or the company themselves. There are methods used by institutions or companies to build their own image. The methods that include the use of brand endorser, changing institution’s layout physically and non- physically as well as improving librarians’ personal branding are used to promote the profession among the public. It is expected that librarian will be known as a profession that is able to represent libraries in the society.